Modified Synthesis and Physicochemical Characterization of a Bioglass-Based Composite for Guided Bone Regeneration - Silva, Marcos José Da; Alves, Wellington; Graeff, Carlos Frederico De Oliveira [UNESP]; D'Alpino, Paulo Henrique Perlatti [UNESP] (Hindawi, 2021)
Objectives. Bioglass composites and polymers are materials of great interest for the medical and dental areas due to their properties, combining the bioactivity of ceramic materials and the mechanical properties of polymers. The purpose of the present study was to develop and to characterize the physicochemical and morphological properties an experimental bioglass-based ternary composite composed associated with sodium carboxymethylcellulose (Na-CMC) and polyvinyl alcohol (PVA). The compatibility of functional groups with bioglass was previously evaluated. The composite was then synthesized and evaluated in terms of morphology, elemental composition, compressive strength, porosity, and bioactivity. Materials and Methods. The bioglass was previously synthesized using a sol-gel route and characterized using FTIR analysis to identify the functional groups. The bone graft composite was then synthesized associating the bioglass with PVA, surfactant Triton X, and Na-CMC. The composite was then morphologically characterized using SEM/EDS. The porosity of the composite was analyzed using μCT, which also provided the composite compression strength. The composite was then evaluated in terms of its bioactivity using SEM/EDS analyses after immersion in SBF for 12, 24, 48, and 72 h. Results. FTIR analysis confirmed, among other components, the presence of Si-O-Ca and Si-O-Si bonds, compatible with bioglass. SEM analysis exhibited a composite with a porous structure without spikes. The elemental mapping confirmed the presence of Si, Ca, and P in the composite. μCT analysis demonstrated a porous structure with 42.67% of open pores and an average compression strength of 124.7 MPa. It has also demonstrated ionic changes in the composite surface after immersion in SBF, with increasing detection of Ca and P as a function of time, highlighting its chemical bioactivity. Conclusions. It can be concluded that the proposed bioglass-based composite presents a three-dimensional, well-structured, chemically bioactive porous structure, mechanically resistant for being reinforced with polymeric phases, with promising results as a synthetic bone graft, which makes it suitable for guided bone regeneration.